PERANCANGAN SISTEM PENGAMAN BUSBAR 150 KV MENGGUNAKAN RELE DIFERENSIAL DI GARDU INDUK SANUR - Ahmad Fauzi; Gede Dyana Arjana; Cok Gede Indra Partha (Program Studi Teknik Elektro UNUD, 2020)
Sanur substation has an important role to fulfill electricity consumption in the Sanurarea and parts of the city of Denpasar. Bursbar is very important part of the performance of asubstation. failures that occur on the busbar can result in widespread blackouts that disrupt thecontinuity of the flow of electric power. A sensitive, selective and fast busbar protection systemis needed to prevent widespread blackouts. This research is designed to design dual 150 kVbusbar protection using differential relays. The power flow and short circuit current in Sanursubstation in this study were analyzed using simulation of load flow and short circuit withcomputer software. Current calculation as the basis for designing and setting differential relaysettings as busbar protection is carried out by the Merz price calculating current method, allcurrents entering and leaving the secured equipment, compared to each other. The busbarprotection system using differential relays was successfully designed with a pick up currentsetting of 0.88 A for busbar A and 1.046 A for busbar B, as well as breakpoints 6 A, slope1;30%, slope2; 135%, and zero seconds working time for both relays the. The differential relaydesigned is able to isolate busbar failures more sensitive, more selective, and faster with aclearing time of 0.035 seconds compared to the existing condition protection system with aclearing time of 1.185 seconds.